Ceramic materials, green compacts, sintered bodies, and articles

JP7643696B2Active Publication Date: 2025-03-11NITERRA CO LTD +1

Patent Information

Application Number
JP2023513030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-08
Filing Date
2022-04-06
Publication Date
2025-03-11
Estimated Expiration
2042-04-06

AI Technical Summary

Benefits of technology

【0014】 (発明の効果) 本発明によれば、主成分としてLa-Mo系複合酸化物を含む抗菌性及び抗ウイルス性に優れたセラミックス材料等を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643696000002
    Figure 0007643696000002
  • Figure 0007643696000003
    Figure 0007643696000003
  • Figure 0007643696000004
    Figure 0007643696000004
Patent Text Reader

Abstract

[Solution] The ceramic material according to the present invention contains a La-Mo-based complex oxide and at least one first element selected from the group consisting of Si and Al. The contained amount of the first element is more than 0 mass% but not more than 0.5 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ceramic materials, green compacts, sintered bodies, and articles. [Background technology]

[0002] As shown in Patent Document 1, ceramics made of composite oxides containing rare earth elements and molybdenum (Mo) are known as new types of inorganic materials with antibacterial and antiviral properties. Among such ceramics, those made of composite oxides containing lanthanum (La) as a rare earth element (for example, La2Mo2O9) have been attracting particular attention because they use lanthanum, which is inexpensive and easily available among rare earth elements, and are therefore advantageous for industrial production. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020 / 017493

[0004] (Problem to be solved by the invention) However, in the past, no consideration was given to what effect the contamination of a composite oxide containing lanthanum and molybdenum with elements other than lanthanum, molybdenum, and oxygen would have on the antibacterial and antiviral properties of the composite oxide. Summary of the Invention

[0005] An object of the present invention is to provide a ceramic material, etc., which contains a La-Mo based composite oxide as a main component and has excellent antibacterial and antiviral properties.

[0006] (Means for solving the problem) As a result of intensive research to achieve the above-mentioned object, the present inventors have found that a ceramic material containing a La-Mo-based composite oxide as a main component has excellent antibacterial and antiviral properties when it contains at least one first element selected from the group consisting of Si and Al in a predetermined ratio, and have completed the present invention.

[0007] The means for solving the above problems are as follows. <1> A ceramic material comprising a La-Mo based composite oxide and at least one first element selected from the group consisting of Si and Al, the content of the first element being greater than 0 mass% and not greater than 0.5 mass%.

[0008] <2> The above does not contain any of the elements of the group consisting of Cd, Hg, Pb, Ra and U. <1> The ceramic material according to claim 1.

[0009] <3> The La-Mo composite oxide is a compound containing La2Mo2O9. <1> or <2> The ceramic material according to claim 1.

[0010] <4> The above <1> from <3> 13. The ceramic material according to claim 12, wherein the ceramic material is in a powder form, and the powdered ceramic material is compressed to form a green compact.

[0011] <5> The above <1> from <3> 13. A sintered body obtained by sintering the ceramic material according to any one of the above items.

[0012] <6> At least a portion of the surface is <1> from <3> 13. An article comprising the ceramic material according to any one of claims 1 to 12.

[0013] <7> The above <1> from <3> 13. An article comprising a substrate and the ceramic material according to any one of the above items dispersed therein.

[0014] (Effects of the Invention) According to the present invention, it is possible to provide a ceramic material and the like which contains a La-Mo based composite oxide as a main component and has excellent antibacterial and antiviral properties. [Brief description of the drawings]

[0015] [Figure 1] Graph showing the results of the antibacterial performance evaluation test of Example 3 [Diagram 2] Graph showing the results of the antiviral performance evaluation test in Example 3 [Diagram 3] Graph showing the results of the antibacterial performance evaluation test of Example 4 [Figure 4] Graph showing the results of the antiviral performance evaluation test in Example 4 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The ceramic material of the present embodiment contains a La-Mo based composite oxide and at least one first element selected from the group consisting of Si and Al, and contains the first element in a predetermined ratio.

[0017] La-Mo based composite oxides are the main components of ceramic materials and are mainly composed of composite oxides of lanthanum (La) and molybdenum (Mo). There are no particular limitations on such La-Mo based composite oxides as long as they do not impair the object of the present invention. Examples of such La-Mo based composite oxides include La2Mo2O9, La2Mo3O 12 , La6MoO 12 , La7Mo7O 30 , La2Mo4O 15 , La2MoO6, La4MoO9 and LaMo2O5, etc. These La-Mo based composite oxides may be used alone or in combination of two or more kinds.

[0018] La-Mo composite oxides include La2Mo2O9 and La2Mo4O 15 , La2MoO6, more preferably containing at least La2Mo2O9, and particularly preferably being La2Mo2O9.

[0019] The La-Mo based composite oxide may be a La-Mo based composite oxide (non-substituted La-Mo based composite oxide) containing only lanthanum (La) and molybdenum (Mo) as metal elements, or may be, for example, a La 1.8 Ce 0.2 The La-Mo based composite oxides, such as Mo2O9, in which part of lanthanum (La) is replaced by other metal elements such as Ce, W, V, etc. (partially substituted La-Mo based composite oxides) may also be used.

[0020] The La-Mo based composite oxide which is the main component is contained in the ceramic material in an amount of at least 99.0 mass %, preferably 99.3 mass % or more, and more preferably 99.5 mass % or more.

[0021] In addition to the La-Mo composite oxide, the ceramic material contains trace elements, which are detected using an X-ray fluorescence spectrometer (XRF) or an inductively coupled plasma (ICP) emission spectrometer (ICP), as described below.

[0022] Examples of the trace elements include a first element consisting of at least one selected from the group consisting of Si and Al. The first element is contained as an essential component in the ceramic material, and the content (content) of the first element in the ceramic material is more than 0 mass% and 0.5 mass% or less. When the content (content) of the first element in the ceramic material is in such a range, phase separation between the La-Mo composite oxide (e.g., La2Mo2O9) and lanthanum aluminate is suppressed, so that it is presumed that excellent antibacterial and antiviral properties can be obtained and the time to develop antibacterial and antiviral properties can be accelerated. Note that since lanthanum aluminate does not contribute to antibacterial and antiviral properties, phase separation from the La-Mo composite oxide causes a decrease in antibacterial and antiviral properties in the ceramic material. If the first element is too much (i.e., if the content (content) of the first element exceeds 0.5 mass%), phase separation occurs between the La-Mo composite oxide and lanthanum aluminate, causing a decrease in antibacterial and antiviral properties.

[0023] In addition, the ceramic material contains the first element in an amount of preferably 0.0001% by mass or more, more preferably more than 0.0003% by mass, even more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more. The first element may be contained in an amount of 0.1% by mass or less, or 0.05% by mass or less.

[0024] The detection of the first element in the ceramic material is first performed using XRF, as described below. When the first element can be detected by XRF, the content (content rate) of the first element in the ceramic material is obtained based on the detection result. When the first element cannot be detected in the ceramic material by XRF, the first element is detected using ICP, as described below, for the ceramic material.

[0025] Examples of other trace elements include a second element consisting of at least one selected from the group consisting of Ca, Mg, Ni, Co, Na, S, Sr, Y, Zn, and B. The second element is preferably contained in the ceramic material at 0.01 mass % or less (100 ppm or less), and more preferably at 0.008 mass % or less (80 ppm or less).

[0026] Detection of the secondary element in the ceramic material is carried out using ICP, as described below.

[0027] Other trace elements include, for example, harmful elements that are of concern for their effects on the human body. In this specification, the harmful elements include Cd, Hg, Pb, Ra, and U. It is preferable that the ceramic material is substantially free of harmful elements. In this specification, "substantially free of harmful elements" means that when the content (content) of trace elements in the ceramic material is evaluated by ICP as described below, the content (content) of harmful elements is below the detection limit.

[0028] Harmful elements, although in extremely small amounts, may be present in raw materials or may adhere to manufacturing equipment (heating furnaces, drying equipment, grinding equipment, etc.) Therefore, ceramic materials that are substantially free of harmful elements can be obtained by selecting high-purity raw materials that do not contain impurities such as harmful elements, or by avoiding the use of manufacturing equipment that may have harmful elements attached to them.

[0029] The ceramic material of this embodiment is manufactured by performing ball mill grinding or mixing (hereinafter, sometimes referred to as "ball milling") using alumina balls for a long period of time (for example, 90 hours) in the manufacturing process of the La-Mo-based composite oxide described later so as to contain the first element at a predetermined ratio. The ball milling may be performed, for example, when mixing the lanthanum compound and the molybdenum compound, or when grinding the powder obtained after the preliminary firing as described later. By performing the ball milling for a long period of time in this way, the ceramic material finally contains a predetermined amount of Al derived from the alumina balls. When silica balls are used, Si is contained in the ceramic material, and when zirconia balls are used, Zr is contained in the ceramic material. Note that, as long as the object of the present invention is not impaired, a predetermined amount of the first element may be supplied to the ceramic material by other methods, such as, for example, containing a predetermined amount of the first element in the raw material in advance.

[0030] In order to set the content (content) of the second element in the ceramic material within the above-mentioned range, for example, when producing a La-Mo-based composite oxide, a high-purity raw material with a low content of the second element (for example, a high-purity molybdenum compound) is used.

[0031] The ceramic material may contain trace elements other than the first element, the second element, and the harmful elements (e.g., Ce (cerium), W (tungsten), V (vanadium), and Gd (gadolinium)) as long as the object of the present invention is not impaired.

[0032] Next, a method for producing the La-Mo based composite oxide will be described.

[0033] The La-Mo based composite oxide is produced through the preparation and firing steps described below.

[0034] The preparation step is a step of mixing a lanthanum compound and a molybdenum compound to prepare a mixed powder.

[0035] The lanthanum compound is a compound containing lanthanum (La) necessary for producing a La-Mo-based composite oxide, and examples thereof include La(OH)3, La2O3, and La2(CO3)3. As the lanthanum compound, for example, at least one selected from the group consisting of La(OH)3, La2O3, and La2(CO3)3 may be used. Note that the lanthanum compound is preferably La(OH)3. The purity of the lanthanum compound is preferably 90.0 mass% or more, more preferably 99.9 mass% or more.

[0036] The molybdenum compound is a compound containing molybdenum (Mo) necessary for producing a La-Mo-based composite oxide, and examples thereof include MoO3, MoO2, MoO, Mo(OH)3, and Mo(OH)5. As the molybdenum compound, for example, at least one selected from the group consisting of MoO3, MoO2, MoO, Mo(OH)3, and Mo(OH)5 may be used. As the molybdenum compound, MoO3 is preferred. The purity of the molybdenum compound is preferably 90.0% by mass or more, more preferably 99.5% by mass or more, and even more preferably 99.9% by mass or more.

[0037] The mixing ratio of the lanthanum compound and the molybdenum compound is preferably adjusted so that the molar ratio of La:Mo is 1:1.

[0038] The lanthanum compound and the molybdenum compound are mixed with each other in a solid phase. The lanthanum compound and the molybdenum compound are both powders, and may be mixed in the powder state, or a solvent such as a lower alcohol (ethanol) may be added to the powders to perform wet mixing. The lanthanum compound and the molybdenum compound may be mixed by wet mixing using, for example, alumina balls (alumina boulders). The wet-mixed mixture (wet mixture) is appropriately dried by water bath drying, spray drying, or the like.

[0039] By such a preparation process, a mixed powder of the lanthanum compound and the molybdenum compound is obtained.

[0040] The firing step is a step of firing the mixed powder obtained in the preparation step in a solid phase state. For example, the firing step is a step of firing the mixed powder in a solid phase state at a temperature condition of 500°C to 700°C for 2 hours or more. The firing step does not need to be performed in a special synthetic air atmosphere, but is performed in a normal air atmosphere.

[0041] This firing step causes the solid-phase lanthanum compound and the solid-phase molybdenum compound in the mixed powder to react with each other, thereby obtaining a powdered La-Mo based composite oxide containing La2Mo2O9 and the like.

[0042] In this specification, the firing step performed to react the lanthanum compound and the molybdenum compound in the mixed powder is sometimes referred to as the “first firing step.” This first firing step is a firing step (calcination step) performed before the powdered La-Mo based composite oxide is sintered.

[0043] After the firing step, a powdered La-Mo composite oxide (sometimes referred to as "La-Mo composite oxide powder") is obtained. The La-Mo composite oxide powder may be granulated by spray drying or the like as necessary to prepare a granular form. For example, a slurry is prepared by adding a solvent such as ethanol to the obtained La-Mo composite oxide powder and carrying out wet mixing and grinding using alumina balls or the like (an example of ball mill processing).

[0044] As described above, by carrying out this wet mixing and pulverization for a long period of time (for example, 90 hours), a predetermined amount of the first element is supplied to the La-Mo based composite oxide.

[0045] The resulting slurry is dried by spray drying or the like to obtain granular La-Mo based composite oxide granulated to a predetermined size.

[0046] As described above, when the La-Mo based composite oxide is produced, a predetermined amount of the first element is supplied, thereby obtaining the ceramic material of this embodiment.

[0047] The La-Mo-based composite oxide containing a predetermined amount of the first element may be sintered to be used as a sintered body. For example, the powdered La-Mo-based composite oxide is compression molded into a predetermined shape (e.g., cylindrical, disk, etc.) using a predetermined press, and the obtained molded body (compressed powder) is fired under a predetermined temperature condition (e.g., 900°C or higher) to sinter, thereby obtaining a sintered body of the La-Mo-based composite oxide (ceramic material) containing a predetermined amount of the first element.

[0048] In this specification, the firing step performed to sinter the La-Mo based composite oxide (ceramic material) may be referred to as the “second firing step.” This second firing step is a main firing step performed to sinter the La-Mo based composite oxide containing a predetermined amount of the first element, and can be performed in an air atmosphere.

[0049] In the manner described above, when the La-Mo based composite oxide is produced, a predetermined amount of the first element is supplied, and thus a ceramic material containing the predetermined amount of the first element is obtained.

[0050] The ceramic material of this embodiment exhibits antibacterial properties (antibacterial activity) and antiviral properties (antiviral activity) in the powder state before sintering. Furthermore, the ceramic material of this embodiment exhibits antibacterial and antiviral properties even after sintering, similar to those before sintering. The method for evaluating the antibacterial and antiviral properties of lanthanum-molybdenum composite oxide will be described later.

[0051] The ceramic material of this embodiment is water repellent. The water repellency is evaluated using a sintered body of the ceramic material. Specifically, the evaluation is performed with reference to JIS R 3257:1999 (Test method for wettability of substrate glass surface). The contact angle of the ceramic material with water is 60° to 110°.

[0052] The ceramic material of the present embodiment may be in the form of a powder, or may be in the form of granules obtained by granulating the powder by spray drying or the like.

[0053] The ceramic material may be used in the form of a green compact obtained by compressing and molding a powdered ceramic material.

[0054] The ceramic material may be used in a sintered state.

[0055] The ceramic material may be used in a form applied to at least a part of the surface of an article. The material constituting the article to which the ceramic material is applied is not particularly limited as long as it does not impair the object of the present invention, and examples thereof include glass, ceramics, synthetic resins such as thermoplastic resins and thermosetting resins, rubber (natural rubber, synthetic rubber), genuine leather (natural leather), synthetic leather, metal-based materials made of metals or alloys, wood, paper, fibers, nonwoven fabrics, silicon (silicon wafers, etc.), carbon materials, minerals, gypsum, etc.

[0056] The ceramic material may be used in a form dispersed in a predetermined substrate. The substrate in which the ceramic material is dispersed is not particularly limited as long as it does not impair the object of the present invention, and examples thereof include glass, ceramics, synthetic resins such as thermoplastic resins and thermosetting resins, rubber (natural rubber, synthetic rubber), synthetic leather, metallic materials made of metals or alloys, paper, fibers, nonwoven fabrics, carbon materials, minerals, gypsum, and the like.

[0057] The present invention will be further described below with reference to examples, although the present invention is not limited to these examples in any way.

[0058] Example 1 La(OH)3 was prepared as the lanthanum compound, and MoO3 was prepared as the molybdenum compound. The purity of MoO3 was 99.5% by mass. Then, the raw material powder of the lanthanum compound and the raw material powder of the molybdenum compound were weighed out so that the molar ratio was 1:2 (La:Mo=1:2). The weighed raw material powders were mixed with a predetermined amount of ethanol, and the obtained wet mixture was dried to obtain a mixed powder (preparation process).

[0059] Next, the mixed powder was calcined (calcined) for 2 hours at 600°C in an air atmosphere to obtain a calcined powder consisting of a reaction product of the lanthanum compound and the molybdenum compound. The calcined powder thus obtained was granulated by the following procedure.

[0060] The mixture was placed in a resin pot together with a predetermined amount of ethanol, and wet-mixed and pulverized (in a ball mill) using alumina balls for 30 hours to obtain a slurry (pulverization step).

[0061] Thereafter, the obtained slurry was spray-dried to obtain the granular ceramic material of Example 1.

[0062] Example 2 The granular ceramic material of Example 2 was obtained in the same manner as in Example 1, except that the raw powder of the lanthanum compound and the raw powder of the molybdenum compound were weighed and mixed in a molar ratio of 2:1 (La:Mo=2:1) ​​and the firing conditions were changed to 650°C for 10 hours.

[0063] Example 3 The granular ceramic material of Example 3 was obtained in the same manner as in Example 1, except that the raw powder of the lanthanum compound and the raw powder of the molybdenum compound were weighed and mixed in a molar ratio of 1:1 (La:Mo=1:1) and the firing conditions were changed to 650°C for 10 hours.

[0064] Example 4 The granular ceramic material of Example 4 was obtained in the same manner as in Example 1, except that MoO3 with a purity of 99.9 mass% was used as the molybdenum compound and wet mixing and grinding (ball milling) using alumina balls was carried out for 90 hours.

[0065] [Identification of La-Mo based composite oxides using XRF] For the ceramic materials of each example, elements contained in the La-Mo based composite oxide were identified using an X-ray fluorescence spectrometer (XRF: X-ray Fluorescence Spectrometry). The measurement conditions were as follows:

[0066] <Measurement conditions> Measurement equipment: Wavelength dispersive X-ray fluorescence analyzer (ZSX-Primus II, manufactured by Rigaku Corporation) Target elements: B to U in the periodic table Measurement range: ppm level to major components Excitation source: Characteristic X-rays (Rh) Measurement diameter: 30mm

[0067] [Detection of trace elements 1] Based on the obtained XRF spectrum, qualitative and semi-quantitative analyses of elements (trace elements) other than lanthanum and molybdenum were carried out on the ceramic material of Example 4. The results are shown in Table 1.

[0068] In addition, elements (trace elements) other than lanthanum and molybdenum could not be detected by XRF spectrum for the ceramic materials of Examples 1 to 3. Therefore, for Examples 1 to 3, elements (trace elements) other than lanthanum and molybdenum were detected by ICP atomic emission spectrometry, which will be described later.

[0069] [Detection of trace elements 2] For the ceramic materials of Examples 1 to 3, elements (trace elements) other than lanthanum and molybdenum were detected by ICP atomic emission spectrometry under the conditions shown below. The contents (ppm) of the main elements with high contents were calculated in terms of oxides. The results are shown in Table 1.

[0070] <Measurement conditions> Measurement equipment: ICP-AES (inductively coupled plasma atomic emission spectrometer (model "iCAP-6500", manufactured by Thermo Fisher Scientific) Sample pretreatment: Nitric acid (hydrochloric acid added) heat decomposition treatment

[0071] [Detection of harmful elements] Whether harmful elements were contained in the ceramics was confirmed from the measurement results (ICP spectrum) of the above-mentioned ICP optical emission spectroscopy for the ceramic materials of Examples 1 to 3. The results are shown in Table 1.

[0072] The ceramic material of Example 4 was examined by the above-mentioned ICP atomic emission spectroscopy to confirm whether harmful elements were contained, as in Example 1. For Example 4, trace elements (secondary elements) were also identified based on the measurement results. The results are shown in Table 1.

[0073] [Antibacterial performance evaluation] The ceramic materials of each example were subjected to an antibacterial performance evaluation test in accordance with JIS Z 2801:2012. Specifically, the antibacterial activity value R after 6 hours was obtained using Staphylococcus aureus as the test bacteria. The antibacterial activity value R was obtained for the action time (after 6 hours) from R=Ut-At. Ut is the logarithmic value (average value) of the number of live bacteria in the unprocessed test sample after the action time t (after 6 hours), and At is the logarithmic value (average value) of the number of live bacteria in the processed test sample after the action time t (after 6 hours). The number of test samples was 3. The test sample was prepared by applying 1.8 mg of the ceramic material in a predetermined dispersion state onto the surface of a glass substrate (50 mm x 50 mm) and drying it (the powder amount per unit area of ​​the test sample was 0.0072 mg / mm 2 ).

[0074] The inoculum concentration was 2.6 x 10 6 cfu / ml, the number of viable bacteria when the inoculum volume is 0.1 ml per sample (cfu / cm 2 The results of the antibacterial activity value R are shown in Table 1.

[0075] The detection limit in the antibacterial performance evaluation was defined as follows: The number of live bacteria at 0 hours was defined as N0, and the number of live bacteria at t hours was defined as N t The survival rate of live bacteria is N t / N0 is the base 10 logarithm, log(N t / N0). Time t is the duration of action. Even if the antibacterial activity value R is 2.0 or more (i.e., R ≥ 2.0), log(N t / N0)-log(N t+1 When / N0)≦0.5, log(N t / N0) and log(N t+1 / N0), whichever is smaller, was used as the detection limit.

[0076] [Antiviral performance evaluation] For the ceramic materials of each example, an antiviral performance evaluation test was conducted in accordance with JIS R 1756:2020 "Visible light responsive photocatalyst, antiviral, film adhesion method". Specifically, the antiviral activity value (in the dark) VD after 6 hours was obtained using bacteriophage Qβ as the test virus. The antiviral activity value (in the dark) VD was obtained for the action time (after 6 hours) by VD = Log (UD) - Log (TD). Log (UD) is the logarithmic value (average value) of the number of phages in the unprocessed test sample after the action time (after 6 hours), and Log (TD) is the logarithmic value (average value) of the number of phages in the processed test sample after the action time (after 6 hours). The number of test samples was 3. The test specimen consisted of a glass substrate (50 mm × 50 mm) on which 1.8 mg of ceramic material was applied in a predetermined dispersion state and then dried (the powder amount per unit area of ​​the test specimen was 0.0072 mg / mm 2 ).

[0077] The concentration of the inoculated phage solution was 2.5 × 10 7 cfu / ml, the number of phages (infectivity value) when the inoculation volume of the inoculated phage solution is 0.1 ml per sample (cfu / cm 2 The results of the antiviral activity value VD are shown in Table 1.

[0078] The lower limit of detection in the evaluation of antiviral performance was defined as follows: The number of phages (infection value) at 0 hours was defined as N'0, and the number of phages (infection value) at t hours was defined as N' t and the phage survival rate N' t / N'0 is log(N' t / N'0). Time t is the duration of action. Even if the antiviral activity value VD is 3.0 or more (i.e., VD ≥ 3.0), log(N' t / N'0)-log(N' t+1 When / N'0)≦0.5, log(N' t / N'0) and log(N' t+1 / N'0), whichever is smaller, was taken as the detection limit.

[0079] [Table 1]

[0080] In Examples 1 to 3, the ceramic materials were prepared using a molybdenum compound (MoO3) with a lower purity than that in Example 4 as a raw material. Therefore, the ceramic materials in Examples 1 to 3 contained Al, Si, Ca, Mg, Ni, Co, Na, S, Sr, Y, Zn, and B as trace elements derived from the raw materials. Thus, the ceramic materials in Examples 1 to 3 contained Al and Si as the first elements at a predetermined ratio. In addition, the contents of the second elements (Ca, Mg, Ni, Co, Na, S, Sr, Y, Zn, and B) in the ceramic materials in Examples 1 to 3 were suppressed to 0.0015 mass% (15 ppm), 0.0007 mass% (7 ppm), and 0.0019 mass% (19 ppm), respectively. It was confirmed that the ceramic materials of Examples 1 to 3 exhibit excellent antibacterial and antiviral properties and also exhibit these antibacterial and antiviral properties quickly.

[0081] Moreover, in Examples 1 to 3, no harmful elements were detected.

[0082] In Example 4, a ceramic material was produced by using a molybdenum compound (MoO3) with a higher purity than those in Examples 1 to 3 as a raw material, and performing wet mixing and grinding (ball milling) using alumina balls when mixing the lanthanum compound and the molybdenum compound for a longer time (90 hours) than those in Examples 1 to 3. Therefore, the ceramic material of Example 4 contains the first elements Al and Si as major trace elements at a content of 0.0403 mass% (403 ppm). These first elements are derived from substances separated from the alumina balls when grinding is performed for a long time using the alumina balls. It was confirmed that the ceramic material of Example 4 has excellent antibacterial and antiviral properties, and that the antibacterial and antiviral properties are developed quickly.

[0083] Furthermore, the results of ICP emission spectroscopic analysis confirmed that the ceramic material of Example 4 contained secondary elements (Ca, Mg, Ni, Co, Na, S, Sr, Y, Zn, and B).

[0084] Moreover, in Example 4, no harmful elements were detected.

[0085] Here, the results of the antibacterial performance evaluation test and the antiviral performance evaluation test of Examples 3 and 4 are compared with the results of the antibacterial performance evaluation test and the antiviral performance evaluation test of Comparative Examples 1 and 2.

[0086] Fig. 1 is a graph showing the results of the antibacterial performance evaluation test of Example 3, and Fig. 2 is a graph showing the results of the antiviral performance evaluation test of Example 3. Fig. 3 is a graph showing the results of the antibacterial performance evaluation test of Example 4, and Fig. 4 is a graph showing the results of the antiviral performance evaluation test of Example 4. In Figs. 1 to 4, the graphs shown with solid lines correspond to the results of Example 3 or Example 4, and the graphs shown with dashed lines correspond to the blank results. The vertical axis of Figs. 1 and 3 represents the number of viable bacteria at elapsed time 0 hours as N0 and the number of viable bacteria at elapsed time t (hours) as N t The survival rate of live bacteria when t / N0 common logarithm (Log(N t 2 and 4, the vertical axis represents the number of phages (infection value) at elapsed time t (hours), with N'0 representing the number of phages (infection value) at elapsed time t (hours), and N' t The phage survival rate N' when t / N'0 common logarithm (Log(N' t / N'0)) and the horizontal axis is the elapsed time t (hours). For Example 4 (Figure 4), the elapsed time t started from 2 hours.

[0087] As Comparative Example 1, a ceramic material prepared by the complex polymerization method described in Patent Document 1 (Example 1 of Patent Document 1) is presented, and as Comparative Example 2, a ceramic material prepared by the solid phase method described in Patent Document 1 (Example 2 of Patent Document 1) is presented.

[0088] In Comparative Example 1 (Example 1 (complex polymerization method) of Patent Document 1), it took 4 hours for Staphylococcus aureus and bacteriophage Qβ (a surrogate for norovirus) to reach the lower limit of detection. In Comparative Example 2 (Example 2 (solid-phase method) of Patent Document 1), Staphylococcus aureus did not reach the lower limit of detection within 6 hours, and bacteriophage Qβ (a surrogate for norovirus) took 6 hours.

[0089] In contrast, in the case of Example 3, as shown in Figures 1 and 2, Staphylococcus aureus and bacteriophage Qβ (a surrogate for norovirus) reached the lower limit of detection in 1 hour. In the case of Example 4, as shown in Figures 3 and 4, Staphylococcus aureus and bacteriophage Qβ (a surrogate for norovirus) reached the lower limit of detection in at least 2 hours. Thus, it was confirmed that Examples 3 and 4 exhibit antibacterial and antiviral properties more quickly than Comparative Examples 1 and 2.

Claims

1. A ceramic material comprising a La-Mo based composite oxide, at least one first element selected from the group consisting of Si and Al, and at least one second element selected from the group consisting of Ca, Mg, Ni, Co, Na, S, Sr, Y, Zn and B, and substantially free of harmful elements from the group consisting of Cd, Hg, Pb, Ra and U, the content of the first element being greater than 0 mass% and not more than 0.5 mass%, and the content of the second element being not more than 0.01 mass%.

2. The La-Mo based composite oxide is 2 M.O. 2 O 9 The ceramic material of claim 1 .

3. The ceramic material according to claim 1 or 2 is in a powder form, A green compact is formed by compressing the powdered ceramic material.

4. A sintered body obtained by sintering the ceramic material according to claim 1 or 2.

5. An article having the ceramic material according to claim 1 or 2 on at least a portion of its surface.

6. 3. An article comprising the ceramic material according to claim 1 or 2 dispersed in a substrate.

Citation Information

Patent Citations

  • Dielectric porcelain composition and dielectric resonator using the same

    JP2000095561A

  • Complex oxide ceramic, method for producing same, and article

    WO2020017493A1

Cited By

  • Antibacterial material, antibacterial material liquid dispersion, antibacterial material dispersion, and method for producing the same

    JP2025113361A